BENCHMARKING AHEPA THESSALONIKI UNIVERSITY GENERAL HOSPITAL’S MEDICAL LIBRARY - Dimitrios , Nikolaos Georgiou (Current Journal of Library and Information Sciences (CJLIS), 2023)
This study delves into a comparative analysis of two distinct time periods in which identical quantitative and qualitative research was conducted to evaluate the efficacy of the Medical Library at Thessaloniki General Hospital AHEPA in Greece. The research seeks to identify the library’s capacity to serve its intended purposes and users effectively. Specialized libraries, particularly in the realm of medical and hospital libraries, play a pivotal role in providing access to essential information and scientific resources for healthcare professionals and individuals with an interest in medical science. Moreover, they extend support to those who may lack direct access to computers, facilitating both work-related tasks and internet usage. The survey comprises two major sections: the first section is dedicated to collecting demographic data from the participants, while the second section encompasses inquiries related to the utilization of the Hospital Medical Library and the perspectives of its users. The research was conducted by disseminating questionnaires to users of the Hospital Library, authorized by the Hospital Scientific Council, spanning a period of approximately two academic semesters. During the first semester, questionnaires were administered to 102 Medical Library users, and during the subsequent semester, the sample size consisted of 100 users, amounting to a total of 202 respondents